The Influence of Company Size, Leverage, Tax Avoidance, and Business Risk on Company Value in Property and Real Estate Companies Listed on the Indonesian Stock Exchange - Amanda Zafira, Giza (Universitas Negeri Padang, 2023)
This research aims to assess the impact of four factors on company value within property and real estate companies listed on the Indonesia Stock Exchange during the years 2018-2022. The factors studied include (1) company size, (2) leverage, (3) tax avoidance, and (4) business risk. The study's population comprises 84 property and real estate companies listed on the Indonesia Stock Exchange. The sample, selected through purposive sampling, consists of companies from the property and real estate sector over a five-year period from 2018 to 2022, resulting in a sample size of 19 companies with a total of 86 observation data points. Multiple linear regression analysis using the IBM SPSS Statistics 25 software is the method of analysis employed. The research findings indicate that (1) company size significantly and positively influences company value, (2) leverage does not significantly affect company value, (3) tax avoidance does not significantly impact company value, and (4) business risk does not significantly affect company value